Analysis of built-up timber columns using matrix progression method - Jumaat, Mohd Zamin (American Society of Civil Engineers, 1991)
Most available methods of predicting the buckling loads of layered and spaced timber columns are analytical methods. These are only suitable for columns with constant number and spacing of connectors in each joint of the columns. For added strength and for practical reasons, columns with additional connectors at the ends are more desirable. This usually requires the use of a numerical method for the prediction of their buckling loads. This paper presents a simple numerical method that can be used on microcomputers to predict the buckling loads of these columns. The method is based on the matrix progression technique. The slip modulus of the connectors adopted in the program is that of the Kuenzi beam on elastic foundation method. To verify the method, 89 layered and spaced timber columns were built and tested. The method was also compared with the Pleskov method.